Tratamento crônico com Decanoato de Nandrolona induz remodelamento cardíaco e renal em ratas, sem modificar parâmetros fisiológicos: o papel do sistema de ANP - Brasil, Girlandia Alexandre (2016)
Anabolic Androgenic Steroids (AAS) are drugs used in an illicit manner, with mostly aesthetic proposes, by both men and women. Due the few researches about the action of these hormones in female cardiovascular system, the aim of the present study was evaluate the effect of chronic treatment with nandrolone decanoate (ND), in high dose in natriuretic peptide system of female rats submitted or not to physical activity and which is the influence of estrogen withdraw for the treatment. For that the animals were randomly divided into 8 groups (n=10 each): SHAM and OVX, were treated with vehicle (peanut oil) twice a week and were not submitted to physical exercise. SE and OVXE, were treated with vehicle and were submitted to resistive physical exercise (5 times a week); SD and OVXD, treated with ND (20mg/kg/week, divided into 2 doses) and were not exercised, and the groups SDE and OVXDE, which were treated and exercised. The OVX animals were submitted to bilateral ovariectomy and the treatments started 21 days after the surgery and were maintained for 4 weeks. After that period, the Bezold-Jarisch reflex (BJR) sensitivity was evaluated by random doses of phenylbiguanide administration. The animals were maintained into metabolic cages for 24h urine collection and after that creatinine, urea and sodium excretion were evaluated. The heart and kidney were maintained in formalin buffer for evaluation of hypertrophy (H/E) and collagen deposition (Picrossirius red) by histology. The right atrium and kidney were frozen in liquid nitrogen for evaluation of genic expression of ANP and NPR-A and NPR-C expression by RT-PCR. After treatment with ND the animals presented increase on genic expression of ANP on atrium and decrease of NPR-A on kidney. The NPR-C shows reduction on the groups that was treated with ND and exercised (SDE and OVXDE).besides that, the treatment promotes hypertrophy and collagen deposition on heart and kidney. Additionally the animals presented muscle hypertrophy (gastrocnemius muscle) and improve on athletic performance observed by increase on jumps/minute on ND treated groups. The treatment decrease estrogen concentration on Sham groups and increase on plasmatic level of testosterone. It was not possible observe change on mean arterial pressure, BJR sensitivity and sodium, creatinine and urea excretion. The ovariectomy little changes the pattern of response to treatment. Thus, we can observe that the treatment with ND changed the ANP system and that result could promote cardio protective effect, observed by not increase on mean arterial pressure and BJR sensitivity.